Application of the gene editing tool, CRISPR-Cas9, for treating neurodegenerative diseases. (January 2018) - Kolli, Nivya; Lu, Ming; Maiti, Panchanan; Rossignol, Julien; Dunbar, Gary L.
Abstract: Increased accumulation of transcribed protein from the damaged DNA and reduced DNA repair capability contributes to numerous neurological diseases for which effective treatments are lacking. Gene editing techniques provide new hope for replacing defective genes and DNA associated with neurological diseases. With advancements in using such editing tools as zinc finger nucleases (ZFNs), meganucleases, and transcription activator-like effector nucleases (TALENs), etc., scientists are able to design DNA-binding proteins, which can make precise double-strand breaks (DSBs) at the target DNA. Recent developments with the CRISPR-Cas9 gene-editing technology has proven to be more precise and efficient when compared to most other gene-editing techniques. Two methods, non-homologous end joining (NHEJ) and homology-direct repair (HDR), are used in CRISPR-Cas9 system to efficiently excise the defective genes and incorporate exogenous DNA at the target site. In this review article, we provide an overview of the CRISPR-Cas9 methodology, including its molecular mechanism, with a focus on how in this gene-editing tool can be used to counteract certain genetic defects associated with neurological diseases. Detailed understanding of this new tool could help researchers design specific gene editing strategies to repair genetic disorders in selective neurological diseases. Highlights: Basic mechanisms and application of the CRISPR-Cas9 system are described. Prospects of CRISPR-Cas9 system to model and treat neurodegenerative diseases have been discussed. Challenges, limitations and inferences from various studies, using the CRISPR-Cas9 have been analyzed and discussed.